4.79+13.6t=6.2+13.7t

Simple and best practice solution for 4.79+13.6t=6.2+13.7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.79+13.6t=6.2+13.7t equation:


Simplifying
4.79 + 13.6t = 6.2 + 13.7t

Solving
4.79 + 13.6t = 6.2 + 13.7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-13.7t' to each side of the equation.
4.79 + 13.6t + -13.7t = 6.2 + 13.7t + -13.7t

Combine like terms: 13.6t + -13.7t = -0.1t
4.79 + -0.1t = 6.2 + 13.7t + -13.7t

Combine like terms: 13.7t + -13.7t = 0.0
4.79 + -0.1t = 6.2 + 0.0
4.79 + -0.1t = 6.2

Add '-4.79' to each side of the equation.
4.79 + -4.79 + -0.1t = 6.2 + -4.79

Combine like terms: 4.79 + -4.79 = 0.00
0.00 + -0.1t = 6.2 + -4.79
-0.1t = 6.2 + -4.79

Combine like terms: 6.2 + -4.79 = 1.41
-0.1t = 1.41

Divide each side by '-0.1'.
t = -14.1

Simplifying
t = -14.1

See similar equations:

| (1+z+z^2+8)/(z+1+8-z+z^2-7z-8) | | -15-4k=-14k+9k+1 | | -8f=16-7f | | 4+12m-2=7m+38-4m | | 16-23= | | 9b-20-14b=13+6b | | 0.8(x-100)=450.00 | | -4(m+1)=-2(m+7) | | 10+9-c=-9+3c | | 5-2*7/2 | | -7-7q=-7-9q | | n/8+4=6 | | 5b^2-34b+24=0 | | x/12=8 | | 5-2*-7/2 | | n/2+4=6 | | 6+d=-10-d | | 17-63= | | x^3-8x^2+4x-32=0 | | n/8+5=10 | | -5-2v=-7v | | 3x+3x+3x=198 | | 6(5-4r)=6(4-5r) | | (4/(x+4))-(3/(x-4))=(2x/((x^2)-16)) | | 10+5v=7v-10 | | 6s+5s=-77 | | -g=g+8 | | -5-3y=-18 | | 8h+8=-2+10h | | 7b-5=2b-.5 | | x^3+4x^2-32x=128 | | x/10-2=4 |

Equations solver categories